Assessment of cash-based pilot school meal program combined with nutrition-sensitive literacy education in Nepal. - Shrestha, Rachana_Manandhar. (Tufts University. Tisch Library., 2019)
This poster assess a cash based pilot school meal program combined with nutrition sensitive literacy education in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy